Depth-to-scalp spatiotemporal dynamics for stereo-EEG - Tal Benoliel; Oshrit Arviv; Diya Doufish; Netaniel Rein; Yuval Harpaz; Evgeny Tsizin; Michal Balberg; Sami Heymann; Zvi Israel; Mordekhay Medvedovsky; Dana Ekstein (Epilepsy & Behavior Reports, 2025)
The data obtained from stereo-elecroencephalography (SEEG) in patients with focal epilepsy are crucial for defining the epileptogenic zone and achieving successful resection, but suboptimal electrode placement impairs SEEG results. We demonstrate an approach for concurrent scalp and depth EEG analysis from one patient with successful intracranial workup and one in whom the seizure onset zone was unsampled by SEEG. Intracranial epileptiform discharges were identified and clustered, their scalp correlates were averaged, and electric source imaging (ESI) was applied to the resulting averaged scalp potential – depth-to-scalp ESI (dsESI). We found temporal differences between intracranial and scalp peaks, as well as variations in averaged scalp spikes morphology and propagation, expressed by their amplitudes and width, and by their jitter across involved electrodes. Put together with the relative degree of focality and location of the averaged scalp spikes’ ESI on the cortex, these data could differentiate onset from propagation of interictal activity and identify unexplored nodes in the epileptic network. Our novel analysis highlights the importance of temporal, and not just spatial, spike dynamics within the epileptic network, may be used to validate depth electrode placement and aid in understanding the epileptic network.